Sistem Pendukung Keputusan Penilaian Pegawai Untuk Kenaikan Jabatan dengan Metode Simple Additive Weighting (SAW) - Milyani Milyani; Yunita Yunita (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
In companies the role of employees is very important. Especially in the assessment of employees for promotion in a company or government agency, an effective and efficient assessment of employees will affect promotions in a company. Usually the company will conduct an employee appraisal for promotion in order to motivate employees to be more active and diligent in their work. Promotion is given to employees on the recommendation of supervisors or supervisors in each part of the work unit based on several assessment criteria. So also happened to PT. Mayora Indah Tbk. Chocolate Division maintenace the production section. Based on research by the author of employee assessments for promotion at PT. Mayora Indah Tbk. The chocolate division of the maintenance section is still subjective. Employee evaluation criteria for promotion at PT. Mayora Indah Tbk. The chocolate division of the production maintenance section is Knowledge, Attendance, Skill, Responsibility, Attitude. The purpose of writing this thesis is one of the graduation requirements for undergraduate (S1) Information Systems study programs at the School of Information and Computer Management (STMIK) Nusa Mandiri Jakarta. In calculating the author uses the Simple Additive Weighting (SAW) method, because this method is suitable for accurate calculations and is very helpful in the process of calculating every data obtained in this research